Acute Myocardial Infarction and Diabetic Ketoacidosis: The Lethal Duo - Kadel, Arun; Thakur, Kartikesh Kumar; Rauniyar, Binay Kumar; Adhikari, Rakesh Bahadur; Limbu, Deepak; Malla, Rabi (Journal of Nepal Health Research Council, 2021)
Diabetes Ketoacidosis in association with acute myocardial infarction is quite frequent but is also associated with higher morbidity and mortality. These two can trigger each other, different hypothesis have been proposed to explain this phenomenon but still it is difficult to know which one appears first. We report a referred case to our centre with acute Myocardial Infarction and diabetic ketoacidosis promptly initiated treatment of diabetic ketoacidosis along with primary PCI. Keywords: Cardiogenic shock; diabetic ketoacidosis; metabolic acidosis; myocardial Infarction